Physiotherapy assessment of breathing pattern disorder: a qualitative evaluation - Lizzie Grillo; Adam Lewis; Anne-Marie Russell; Harriet Shannon (BMJ Open Respiratory Research)
Objectives To explore physiotherapists’ opinions of physiotherapy assessment of Breathing Pattern Disorder (BPD).Methods Qualitative study using focus groups (FGs) with reflexive thematic analysis and survey methods. The survey was distributed via social media and email to UK specialist physiotherapy interest groups. Two FGs, conducted in different settings, included physiotherapists based in hospital outpatients/community, private practice and higher education.Results One-hundred-and-three physiotherapists completed the survey. Respondents identified a lack of consensus in how to define BPD, but some agreement in the components to include in assessment. Fifteen physiotherapists participated in the FGs. Three themes emerged from FG discussions: (1) nomenclature and language of breathing, (2) BPD and breathlessness and (3) The value of assessment of breathlessness.Conclusion The inconsistent nomenclature of dysfunctional breathing pattern impacts assessment, management and understanding of the diagnosis. Clarity in diagnosis, informing consistency in assessment, is fundamental to improving recognition and treatment of BPD. The findings are useful in the planning of education, training, future research and guideline development in BPD assessment.